Kehandalan Pelayanan Kartu Indonesia Sehat di Kelurahan Kameloh Baru Kecamatan Sabangau Kota Palangka Raya - Indah Tri Handayani; Siti Alimah (Pencerah Publik, 2016)
The purpose of this research is to know and to describe the reliability of Indonesia's Healthy card service in the new Office Kameloh Sabangau District of Palangka Raya. The type of research used in this study is descriptive. Using qualitative research methods. The type of data in this study is primary data that includes social welfare officers, Lurah and the new District Community Kameloh Sabangau Palangka Raya. Secondary data comes from documentation, other data sources, data collection techniques using interviews, observations, and documentation. Based on the results of the reliability of this research service provided by the Social Welfare section of the new Kameloh village of Sabangau of Palangka Raya, still not in accordance with the expectations of society can be seen from within the ability and Reliability to provide reliable service that the village is still not able to take responsibility in completing its task. The accuracy or thoroughness of staff in serving the community or service users is still not careful and thorough. Because there are still many complaints of people or customers about the lack of accuracy and thoroughness of employees in the writing of names, in examining the community files and resolving community files